Pattern and effect of economic agglomeration in the Yangtze River Delta region based on population-land allometric growth - Zhu, Yiheng; Yang, Shan; Lin, Jinping; Cai, Anning (Frontiers in Earth Science, 2023)
The speed of urban growth affects urban development's momentum and urban agglomeration's spatial state. The influence of the asymmetric flow of population and land factors on the economic agglomeration effect is an essential issue in the coordinated development of urbanization. To study its impact on the orderly development of China's urban economy, this paper selects 41 cities in the Yangtze River Delta (YRD) region, measuring the spatial and temporal evolution of the allometric growth relationship between population and land, explores the mechanism of the effect of allometric relationships on the economic agglomeration effect. The results show that: (1) Population-land allometric growth is characterized by a transition from population to land expansion. The transition phase is divided into six stages, from positive to negative allometric growth. In terms of scaling coefficients, the period from 2000 to 2011 is characterized by negative allometric growth, and the period from 2012 to 2019 is characterized by positive allometric growth. Spatially, the Shanghai metropolitan area evolves into a positive allometric primary stage, while the core and central areas evolve into a positive allometric secondary stage, with the latter's development transition lagging behind the former by about ten years. (2) The spatial dependence of economic agglomeration in the YRD is strong, showing a spatial distribution trend of "high in the middle, low in the north and south, high in the east and low in the west", the agglomeration gap is gradually reduced, forming a "continuous area of high-value economic agglomeration" with the core area as the center and spreading outward, reflecting the efficacy of the YRD integrated development strategy. (3) The economic agglomeration effect of allometric growth is classified into four types: positive-allometric positive-effect, positive-allometric negative-effect, negative-allometric positive-effect, and negative-allometric negative-effect. In the YRD region, 70.7% of the cities have positive effects, of which 93.1% are positive-positive. (4) The allometric growth has an important impact on the reconfiguration of economic agglomeration pattern, 78% of the cities in the study period produced leapfrog movements in different quadrants, and the incongruity between population growth and land expansion should be actively regulated in the future.